Hybrid layer thickness and resin tag length of a self-etching adhesive bonded to sound dentin - Sundfeld, Renato Herman [UNESP]; Valentino, T. A.; de Alexandre, R. S.; Briso, André Luiz Fraga [UNESP]; Sundefeld, Maria Lúcia Marçal Mazza [UNESP] (Elsevier B.V., 2005)
Objectives: the purpose of this study is to employ optical microscopy to measure the thickness of the hybrid layer and the penetration (tags) of an aggressive self-etching adhesive system into sound dentin.Methods: occtusat cavities were prepared in 40 extracted human posterior teeth. The prepared teeth were randomly assigned to four experimental groups with 10 specimens each. The self-etching adhesive system Adper Prompt L-Pop was applied to the dentin surface as follows: Group 1: cavosurface enamel was etched for 60 s and dentin for 20 s with 35% phosphoric acid get, immediately followed by application of the self -etching adhesive with a brush to the entire cavity for 15 s; Groups 2, 3, and 4: no pre-etching was performed, and the self -etching adhesive was applied to both enamel and dentin for 15, 30 and 45 s, respectively. After curing, the cavities were fitted with composite resin Fittek Z250. Afterwards, the teeth were decalcified and the restorations were carefully removed for later embedding in paraffin. The specimens were serially sectioned at 6 mu m of thickness and sequentially mounted in glass slides. These sections were stained with Brown and Brenn staining for posterior analysis and measurement of the hybrid layer and resin tags on a tight microscope with a micrometric ocular 40/075. The results were submitted to analysis of variance at the 5% level.Results: whenever there was significance, the Tukey test was applied at the 5% level. The specimens receiving application of acid etching before the selfetching. adhesive displayed a larger thickness of the hybrid layer; on the other hand, specimens receiving only application of the self -etching adhesive on dentin for 15, 30 and 45 s exhibited similar thickness of the hybrid layer. As regards the resin tags, no statistically significant differences could be found between the study groups.Conclusions: it could be concluded that the increase in the time of application of the self-etching adhesive Adper Prompt L-Pop did not significantly influence the formation and thickness of hybrid layer, as well as its penetration into the sound dentin surface. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: dentin; self-etching adhesive; hybrid layer; tags; optical microscopy